Determination Leadership, Compensation, Organizational Culture on Health Madani through Performance of Public Hospital in Batam - Faizah, Ana; Nurhatisyah; Yanti, Sri; Puspita Dewi, Nolla; Wibisono, Chablullah (International Journal of Psychosocial Rehabilitation, 2020)
The Vision of Batam is "The Realization of The City of Batam as a Modern World Level Bandar Madani and becomes a Locomotive of the National Economic Growth," which is must be based on health. The hospital as the spearhead of the leading health care services, there are two kinds of the hospital in Batam, Public and Private Hospital. The orientation performance of hospitals is undoubtedly influenced by the spirit and variable determiner of the hospital's performance, so this study aims to: "determine the Leadership, Compensation, and Culture on Health Madani through Performance of Public Hospitals in Batam". The study population was all over the State Civil Apparatus in a public hospital, using the formula of Slovin as the sample of 185 respondents. Data were analyzed using Structural Equation Model (SEM). The research proves that Leadership, Compensation, and organizational culture on Health of Madani through the Performance of a Public Hospital have a significant Effect, except leadership on performance and compensation on health Madani. Pursuant to the result of this study, it is suggested that management of the hospital in order to have a spirit of service so that health of Madani or Civil Society, which is "Healthy, Self-reliant and Equitable People," can be reached.